Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Kemampuan Membaca Al-Qur’an Peserta Didik Melalui Metode Menghafal (Penelitian Di SMPIT Tahfidzul Qur’an Ihya As-Sunnah Tasikmalaya - Mardani, Dede Aji; Imas Siti Masuroh (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2024)
This problem is motivated by the fact that many students experience difficulties in learning religion, especially in learning to read and memorize the Qur'an, but this difficulty is not yet known with certainty the causal or inhibiting factors that make students experience difficulties in reading the Qur'an. This research aims to find out: 1) the implementation of the teacher's efforts in improving the ability to read and memorize the Qur'an at SMPIT Tahfidzul Qur'an Ihya As-sunnah Tasikmalaya. 2) supporting and inhibiting factors for the implementation of reading and memorization at SMPIT Tahfidzul Qur'an Ihya As-sunnah Tasikmalaya. 3) This research uses qualitative methods, research that bases its analysis not derived from statistical calculations. Data obtained through interviews, observation and documentation. Data analysis used is depenelitiantif analysis. The results showed that, The process of implementing the pakistani method in memorizing the Qur'an at SMPIT Tahfidzul Qur'an Ihya As-sunnah Tasikmalaya by using the pakistani method or better known as the sabaq, sabqi, and manzil method has gone well even though it is still not perfect. this shows that through the pakistani method (sabaq, sabqi, manzil) students are more active, enthusiastic and focused on what the teacher teaches.